INVESTIGATION OF THE USE OF SCRAP TYRES AS SOIL REINFORCEMENT - TAHER, SHAAFAN ABDULLAH; HASSAN, HUSSEIN JALAL ASWAD; FARAMARZI, ASAAD (Journal of Duhok University, 2021)
Waste tyres, which are produced in every society in numbers that are increasing annually, are impacting the environment and causing serious problems. These materials possess exceptional properties that can be reused as reinforcement materials in the geotechnical engineering industry. This study investigated the effects of tyre shreds that were randomly mixed with sand and clay to enhance their engineering properties. An Atterberg limits analysis, as well as compaction and odometer tests, were performed on china clay with scrap tyres of varying weights (10, 20, 30 and 40%). The results show that the Atterberg limits of clay decrease in proportion to increases in the volume of tyre shreds. The compaction characteristics of clay decreased with increased tyre-shred contents of 2–6 mm and 12 mesh. Compression and recompression indexes increased gradually with the tyre-shred content of 12 mesh. A series of direct shear strength tests were performed on the sand-shredded tyre mixtures of Levenseat sand and concrete sand using a direct shear box of 10 cm x 10 cm. Two relative sizes of shredded tyres, 12 mesh and 2–6 mm, were mixed with sand of different weight percentages. The results showed a general increase in the shear strength parameters of both types of sand with the addition of the shredded tyres. The maximum shear strength was obtained at optimum shredded tyre content, approximately 20% for the 2–6 mm shreds and 15% for the 12-mesh shreds. The results showed that it is possible to use shredded tyres in geotechnical applications